Green synthesis of PLGA and fabrication of topotecan and thymoquinone dual anticancer drug loaded PLGA nanoparticles: a controlled release study for cancer therapy - Srilatha Cheekuramelli, Naga; Muhammed, Hasin N.; Garnaik, Baijayantimala; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Cancer therapy is often hindered by poor solubility, low bioavailability, drug resistance, and tumor microenvironmental barriers associated with conventional chemotherapeutics. Polymeric nano-drug delivery systems offer a promising strategy to overcome these limitations, particularly for synergistic multi-drug delivery. In this study, a biodegradable and biocompatible PLGA copolymer (70:30, M-w approximate to 14,500) was synthesized by ring-opening polymerization using zinc proline complex as an initiator through a green route. The copolymer's potential for delivering topotecan (TPT), a water-soluble chemotherapeutic, thymoquinone (TQ), a poorly water-soluble chemotherapeutic, and their combination (TPT+TQ) for cancer treatment was investigated. These nanoparticles demonstrateda consistent particle size < 200 nm high encapsulation efficiency along with desirable controlled-release attributes. Moreover, they exhibited specific release characteristics and cytotoxic effects against HeLa cells, achieving an IC50 value of 20.88 M for the combination therapy (TPT+TQ). Additionally, cytocompatibility testing on L929 fibroblasts confirmed over 98% cell viability for blank PLGA nanoparticles. Additionally, confocal imaging studies confirmed efficient cellular uptake and nuclear localization of the nanoparticles. Overall, the PLGA based dual drug loaded nanoparticles presents a promising approach for targeted, synergistic co-delivery, potentially improving efficacy and reducing toxicity in cancer therapy.
Keywords: Biodegradation; dual drug-loading; PLGA copolymer; thymoquinone; Topotecan